OERs, standards and trends [OER, estándares y tendencias] - Rodriguez Morales, G. (2009)
The terms learning objects (LOs) and open educational resources (OERs) are of interest in many areas of society, particularly in higher education, offering a valuable opportunity for equity and social justice through access, implementation and knowledge generation. For OERs to provide designers and users with all its advantages and features such as reusability, accessibility, interoperability, and applicability in the context of the objectives set for its creation, they must be aligned with the trends and developments in society as an end with technology as a medium. This paper presents research on three aspects of the future possibilities of OERs: accessibility standards, the incorporation of social components and the semantic web. Integrating social tools encourages the active involvement of OER designers and users, which in turn brings about collaborative learning. The creation of OER material is also faster, with easier access to them through search engines linked to educational platforms and social tools (Web 2.0). In addition, social tagging by users adds descriptive metadata to the OERs. Finally the use of intellectual property licenses which acknowledges the authors and allows free use of the material should be considered.